The Development of Community Strengthening Model to Prevent Road Traffic Accidents in Ban Ped Sub-district, Mueang District, Khon Kaen Province - Phinyo, Piyanuch; Phinyo, Kittipoom; Thipornphan, Klauymai; Shawong, Prapatsri (Nursing Journal CMU, 2022)
The objectives of this community-based participatory action research were 1) to study the situation of road accidents; 2) to develop a community strengthening model for the prevention of road accidents; and 3)to evaluate the results of the operation’s community strengthening to prevent road traffic accidents at Ban Ped Community (4 communities). The driving team consisted of 60 people, including the community leader, village health volunteers, Senior Club members, Local Authority Organization staff, Tambon Health Promoting Hospital staff, Elementary School and Secondary School staff and the police staff; the operating team consisted of 64 people, including children and youths from the elementary and secondary schools. The research tools included 1) a road accident record form; 2) group discussion guidelines; and 3) a questionnaire on knowledge, attitudes, and riding behavior. The tools’ content validity was checked by three experts and their reliabilities were .70, .86, and .76, respectively. The study was conducted in four steps, and the driving team participated in all of these steps: 1) analyzing the problem situation; 2) planning to prevent road accidents; 3) carrying out the operation; and 4) evaluating the operation. The quantitative data was analyzed using descriptive statistics, and the qualitative data was analyzed using content analysis. The research results were as follows: 1. According to the situation of road accidents, it was found that 79.59% of road accidents were caused by motorcycles. In addition, 80.49% of riders having road accidents were between 10-29 years, and 82.8% of them did not wear a helmet. Moreover, 96.9% of them had a low level of riding knowledge, while 76.6% had a low level of attitude, and 50.0% had a low level of riding behavior. 2. The community strengthening model for the prevention of road accidents consisted of 5 components: 1) Creating a mechanism to drive the prevention of road accidents in the community; 2) developing the accident information system; 3) meeting to prepare road accident prevention plans; 4) capacity-building to prevent road accidents; and 5) reporting or reporting on road accidents. 3. The results of the operation’s evaluation were as follows. After participating in the project, 1) helmet wearing increased to 82.8%; 2) knowledge increased from a low level to a high level (76.6%); attitude increased from a low level to a high level (82.2%); and riding behavior to prevent road accidents increased from a low level to a moderate level (54.7%); and 3) the rate of road accidents decreased from 0.14% to 0.03%. From the results of this study, it is recommended that this model should be expanded and applied to all communities in the sub-district.